2009
DOI: 10.1101/lm.1254209
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CREB-dependent gene expression increases the excitability of neurons in the basal amygdala and primes the consolidation of contextual and cued fear memory

Abstract: Regulated expression of a constitutively active form of cAMP response element-binding protein (CREB), VP16-CREB, lowers the threshold for the late phase of long-term potentiation in the Schaffer collateral pathway in a de novo gene expression-independent manner, and increases the excitability and reduces afterhyperpolarization of neurons at the amygdala and the hippocampus. We explore the consequences of these changes on the consolidation of fear conditioning and find that the expression of VP16-CREB can bypas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 36 publications
7
81
0
2
Order By: Relevance
“…Extensive studies have shown that CREB is not only a requirement but also a critical driving force for the consolidation of long‐term conditioned fear memories (Bourtchuladze et al ., 1994; Kida et al ., 2002; Viosca et al ., 2009; Zhou et al ., 2009). We investigated whether decreased PKA‐CREB signaling induced by decreased O‐GlcNAcylation affects auditory fear conditioning in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have shown that CREB is not only a requirement but also a critical driving force for the consolidation of long‐term conditioned fear memories (Bourtchuladze et al ., 1994; Kida et al ., 2002; Viosca et al ., 2009; Zhou et al ., 2009). We investigated whether decreased PKA‐CREB signaling induced by decreased O‐GlcNAcylation affects auditory fear conditioning in mice.…”
Section: Resultsmentioning
confidence: 99%
“…A third probe trial ( (Martin and Morris 2002;Diamond et al 2004). Interestingly, we have also observed that the expression of VP16-CREB bypassed the requirement for de novo gene expression associated with longterm memory formation in contextual and cued fear conditioning tasks, suggesting that CREB-dependent gene expression can be sufficient for fear memory consolidation (Viosca et al 2009). The effects in fear memory consolidation and spatial memory retrieval observed in mice with enhanced CREB activity might have a physiological correlate in normal behaving animals.…”
Section: Discussionmentioning
confidence: 99%
“…These have contributed importantly to clarify the role of CREB in the consolidation of different forms of memory (Josselyn et al 2001;Mouravlev et al 2006;Brightwell et al 2007;Restivo et al 2008;Viosca et al 2009), but have not as yet been applied to explore the role of CREBdependent gene expression in spatial memory in the Morris water maze. To explore the consequences of chronic enhancement of CREB function on spatial memory, we examine spatial navigation in bitransgenic mice that express in a regulated and restricted manner a constitutively active form of CREB, VP16-CREB, whose strong transactivation activity is independent of the signaling cascades that regulate wild-type CREB (Barco et al 2002).…”
mentioning
confidence: 99%
“…Passive avoidance experiments were performed with a moderate (0.4 mA) and a strong (0.8 mA) electric stimulus (Viosca et al, 2009), both well above the pain threshold (Fig. 5A).…”
Section: Passive Avoidancementioning
confidence: 99%